Manhattan Project 1940s research on the prompt fission neutron spectrum - Chadwick, Mark B.; Capote, Roberto (Frontiers in Physics, 2023)
We describe how the prompt fission neutron spectrum (PFNS) was determined for the Manhattan Project at Los Alamos. Early work before Word War II at American and British universities is described, together with theoretical work by Feather at Cambridge and Bethe at Los Alamos. As the Manhattan Project was being planned in1942, two experiments on natural uranium were commissioned that proved to be influential: (1) An integral experiment at Chicago by Christy and Manley that accurately determined the average PFNS spectrum energy, 2.2 $±$0.2 MeV; (2) Bloch and Staub's Stanford cyclotron measurement of the PFNS spectrum, which obtained an average energy of 1.70 $±$0.34 MeV. These two papers, previously unavailable outside of Los Alamos, are reproduced in the Appendix. From these data, at the beginning of the project in 1943 Serber estimated an average $^{235}$U PFNS energy of 2 MeV, and indeed this agrees with today's best estimate. The challenges facing the scientists involved both the availability of only very small samples of enriched uranium and plutonium targets, and neutron detection technologies. During the project, $^{235}$U and $^{239}$Pu PFNS were measured by Nicodemus and Staub. These also proved to be quite accurate and gave an average spectrum energy of 2 MeV for $^{235}$U. (This is not reproduced in the Appendix because it was published after the war in Physical Review 89, 1288 (1953)). New methods were developed to enable more accurate measurements, and this paper describes how the PFNS was determined surprisingly well by 1945. We end by describing the PFNS data used by Ford and Wheeler in their simulations in 1951. We compare the measurements with our best understanding today as embodied in the Evaluated Nuclear Data File ENDF/B-VIII.0. Some images from historical documents in our Los Alamos National Security Research Center (NSRC) archives are shown.